EXT1 and EXT2 Variants in 22 Chinese Families With Multiple Osteochondromas: Seven New Variants and Potentiation of Preimplantation Genetic Testing and Prenatal Diagnosis - Wang, Ye; Zhong, Liangying; Xu, Yan; Ding, Lei; Ji, Yuanjun; Schutz, Sacha; Férec, Claude; Cooper, David N.; Xu, Caixia; Chen, Jian-Min; Luo, Yanmin (Frontiers in Genetics, 2020)
Multiple osteochondromas (MO), the most common type of benign bone tumor, is an autosomal dominant skeletal disorder characterized by multiple cartilage-capped bony protuberances. In most cases, EXT1 and EXT2, which encode glycosyltransferases involved in the biosynthesis of heparan sulphate, are the genes responsible. Here we describe the clinical, phenotypic and genetic characterization of MO in 22 unrelated Chinese families involving a total of 60 patients. Variant detection was performed by means of a battery of different techniques including Sanger sequencing and whole-exome sequencing. The pathogenicity of the missense and splicing variants was explored by means of in silico prediction algorithms. Sixteen unique pathogenic variants, including 10 in the EXT1 gene and 6 in the EXT2 gene, were identified in 18 (82%) of the 22 families. Fourteen (88%) of the 16 variants were predicted to give rise to truncated proteins whereas the remaining two were missense. Seven variants were newly described here, further expanding the spectrum of MO-causing variants in the EXT1 and EXT2 genes. More importantlyFinally, the identification of causative variants allowed us to provide genetic counselling to 8 MO patients in terms either of preimplantation genetic testing (PGT) or prenatal diagnosis, thereby preventing the reoccurrence of MO in the respective correspondingaffected families. This study is the first to report the successful implementation of PGT in MO families and describes the largest number of subjects undergoing prenatal diagnosis to date.